Idiopathic Membranous Nephropathy: Glomerular Pathological Pattern Caused by Extrarenal Immunity Activity - Liu, Wenbin; Gao, Chang; Dai, Haoran; Dong, Zhaocheng; Zheng, Yang; Gao, Yu; Liu, Zhiyuan; Feng, Zhendong; Tian, Xuefei; Liu, Baoli (Frontiers in Immunology, 2020)
Idiopathic membranous nephropathy (IMN) is a pathological pattern of glomerular damage caused by autoimmune response. Immune complex deposition, thickness of glomerular basement membrane and changes in the podocyte morphology are responsible for the development of proteinuria, which caused by targeted binding of auto-antibodies to podocytes. Several auto-antigens have been recently identified in IMN, including M-type receptor for secretory phospholipase A2 (PLA2R1), thrombospondin type-1 domain-containing 7A (THSD7A) and neural epidermal growth factor-like 1 protein (NELL-1). Measurement of peripheral circulating antibodies has become an important clinical reference index. However, some clinical features of IMN remain elusive and need to be further investigated, such as the autoimmunity initiation, IgG4 predominance, spontaneous remission, and the unique glomerular lesion, and so on. Given these unresolved issues closely be related to the clinical practice, we have proposed a hypothetical pathogenesis model of IMN, which can be summarized as: induced by environmental stimuli or other cause, the PLA2R1 antigen and/or THSD7A antigen exposed to the extrarenal tissues such as lungs, followed by producing the auto-antibodies that target and damage to the podocytes by circulation. In this review, we highlighted the potential association between environmental stimuli, immune activity and glomerular lesion, the underlying basis for spontaneous immune and proteinuria remission.